Are ICT good partners for the development of creativity? A systematic review of literature. (25th March 2019) - Angarita, Ludwig Markbent; Chiappe, Andrés
Creativity is considered one of the key skills of the 21st century. Likewise, information and communication technologies (ICT) have been identified as a constant presence in contemporary education, where there is the persistent challenge of developing creative thinking in children and young people who will live and perform in a highly globalised, interconnected, changing and uncertain social and cultural context. To better understand the relationship between the educational use of ICT and the development of creativity, a systematic literature review was carried out on 100 published studies with this subject. The results highlight on the one hand, the coexistence of three different conceptualisations on creativity and on the other hand, the identification of both contributions and barriers of ICT to the development of creative thinking that have more to do with cultural, attitudinal and organisational issues about their educational use than with the very nature of ICT.